Ahl Al-Hadith and Ahl Ar-Ra’yi in the Formation and Development of Islamic Law - Anwar, Saiful; Malik, Deden Abdul; Zulvia, Ransya Ayu; Fauziansah, Silvanus; Fitrianto, Bambang; Anwar, Syahrul (NAJAHA, 2024)
This study aims to analyze the role and contribution of Ahl Al-Hadith and Ahl Ar-Ra’yi in forming and developing Islamic law. These two groups of thought emerged in the 2nd century Hijriah with different approaches to interpreting the sources of Islamic law. This study uses a qualitative research type with a descriptive-analytical approach. The primary data in this study are classical and modern literature relevant to the thoughts of Ahl Al-Hadith and Ahl Ar-Ra’yi. Data sources include classical Islamic law books, books, and scientific articles that discuss the methodology of these two groups. Data collection techniques are carried out through library research by analyzing primary and secondary texts. The collected data are analyzed using content analysis techniques, which aim to explore the methodological patterns of the two groups in interpreting Islamic law. The study results show that despite having different methodological approaches, both seek to uphold Islamic law by maqashid al-sharia. Ahl Al-Hadith contributed to the birth of the Maliki and Hanbali schools, emphasizing the text's authority. At the same time, Ahl Ar-Ra’yi played a role in introducing the flexible ijtihad method popularized by Abu Hanifah. This approach was later balanced by Imam Syafi'i, who integrated text and reason into his ushul fiqh. This study concludes that the differences in methodology between Ahl Al-Hadith and Ahl Ar-Ra’yi not only enrich the treasury of Islamic law but also provide a mechanism for adapting Islamic law to changing times while maintaining the basic principles of sharia.